Effect of prewarmimg on body temperature and shivering in total knee arthroplasty patients after surgery - Sukanthachalathon, Ratchanee; Asdornwised, Usavadee; Thosingha, Orapan; Vichitvejpaisal, Phongthara (Chulalongkorn Medical Journal, 2021)
Background: Inadvertent hypothermia and shivering is recognized risk in surgery. Core temperature in patients warmed with forced air warming remains poorly characterized. The incidence in patients with total knee arthroplasty (TKA) leading to intraoperative hypothermia 43.9%. Objectives: This quasi-experimental research study was conducted to compare body temperature and shivering after surgery in patients with total knee arthroplasty who received prewarming and those who received routine nursing care. Methods: Thirty-first patients were randomly assigned for experimental group and Thirty-first patients for control group. Data were collected by the following tools and methods, namely: patient demographic and clinical characteristic records, tympanic membrane thermometer, ambient temperature and humidity meter and the wrench’s scale. Data were analyzed by using One-way analysis of covariance (ANCOVA) to compare the differences between the means of body temperature both groups and shivering was analyzed by Chi-square test. Results: Body temperature in the experimental group was higher than the control group at the time before discharged from the operating room (P < 0.001), at the time they entered the recovery room (P = 0.001) and at 30 minutes after they transferred to the recovery room (P < 0.001) and 60 minutes after they transferred to the recovery room (P = 0.001). The means of body temperature before returning to the recovery room of both groups were not significantly different (P = 0.391). In addition, the shivering in the experimental group was significantly lower than the control group at time that entered to the recovery room (P = 0.009) and at 30 minutes after transferred to the recovery room (P = 0.002). The means temperature at 60 minutes after transferred to the recovery room the experimental group and control group were not significant difference (P = 0.1). Conclusion: Prewarming was more effective than not prewarming in the prevention of postoperative hypothermia and shivering in TKA.